Nanopartículas magnéticas de 'FE''CO'@'AU': preparação, caracterização e funcionalização com complexo de 'RU'(II) luminescente - Silva, Maria Aparecida Santiago da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Nanomaterials with magnetic and luminescent properties conjugated in core@shell type nanostructures, also called magneto-luminescent or magneto-optical, have been prepared and are promising as new bimodal agents for applications in bio-imaging. In synthesized core@ shell nanostructures, FeCo alloy magnetic particles were used as magnetic core, because they presente high values of saturation magnetization (MS) in small dimensions, while the gold was chosen as the material for their shell because of its biocompatibility and its surface chemistry that allow the incorporation of new biomolecules and molecular structures in the hybrid core@shell optical components. Different nominal percentage compositions FeCo particles (Fe60Co40, Fe50Co50, Fe40Co60) were prepared by the modified polyol method, using a reducing atmosphere of H2. XRD and ICP-AES analyzes confirm the formation of FeCo alloy, however the particles are likely rust when in contact with air for prolonged periods. The layer of iron oxide on the surface of the particles was confirmed by Mössbauer spectroscopy. Through these measures, we observed for low Fe content FeCo particles greater resistance to surface oxidation upon exposure to air. The magnetic hysteresis curves from vibrating sample magnetic measurements (VSM) suggest the ferromagnetic behavior for all samples. The higher value of Ms (203 emu/g) was obtained for Fe40Co60 particles and it is close to reported one to massive alloys with the same composition. Concurrently, a slight hysteresis loop displacement along the applied field axis is observed in all samples as a result of polarization exchange phenomenon or exchange- bias, which indicates the formation of an oxide layer on the FeCo alloy particles surface and corroborates the observed XRD and Mössbauer data. FeCo particles were coated by an Au layer by the seed-mediated growth method. Molar ratios of FeCo:Au were set to 5:1, 3:1, 2:1 and 1:1 by varying the Au (III)...

Nanomateriais com propriedades magnéticas e luminescentes conjugadas em nanoestruturas do tipo caroço@casca, também chamados de magneto-luminescentes ou magneto-óticos, foram preparados e são promissores como novos agentes bimodais para aplicações em bioimagem. Nas nanoestruturas caroço@casca sintetizadas, partículas magnéticas da liga FeCo foram utilizadas como caroço magnético, por apresentarem altos valores de magnetização de saturação (MS) em dimensões reduzidas, enquanto que o ouro foi escolhido como material para a casca, devido à biocompatibilidade e à química de superfície que possibilitam a incorporação de biomoléculas e de novos componentes óticos moleculares nas estruturas híbridas. As partículas de FeCo de composições percentuais nominais distintas (Fe60Co40, Fe50Co50, Fe40Co60) foram preparadas pelo método do poliol modificado, utilizando atmosfera redutora de H2. As análises de difração de raios X e de ICP-AES confirmam a formação da liga FeCo, contudo as partículas são susceptíveis à oxidação, quando em contato com ar por períodos prolongados. A camada de óxido de ferro na superfície das partículas foi confirmada através da espectroscopia Mössbauer. Através dessas medidas, foi possível verificar para as partículas de FeCo com baixo teor de Fe, uma maior resistência à oxidação da superfície, após exposição ao ar. As curvas de histerese obtidas através das medidas magnéticas de amostra vibrante (VSM) sugerem o comportamento ferromagnético para todas as amostras. O maior valor de MS (203 emu/g) foi obtido para partículas Fe40Co60 e está próximo do valor relatado para ligas massivas com mesma composição. Concomitantemente, um leve deslocamento do ciclo de histerese, ao longo do eixo do campo aplicado, é observado, em todas as amostras, como uma consequência do fenômeno de polarização de troca ou exchange-bias, o que indica a formação de uma camada de óxido sobre a...
Keywords: Físico-química; Materiais magneticos; Luminescencia; Ligas de ferro; Ouro; Nanopartículas; Gold